Supermode spatial solitons via competing nonlocal nonlinearities - Jung, Pawel Stanislaw; Karpierz, Miroslaw; Trippenbach, Marek; Christodoulides, Demetrios; Krolikowski, Wieslaw (Photonics Letters of Poland, 2018)
We study spatial soliton formation in a system with competing nonlinearities. In doing so, we consider a specific nonlinear response that involves both focusing and defocusing nonlocal contributions. We demonstrate that at a sufficiently high input power level, the interplay between these nonlocal nonlinearities may lead to the formation of in-phase, two-hump, fundamental spatial solitons. The conditions required for the existence of these two-peak spatial solitons are also presented. Full Text: PDF References G. Stegeman and M. Segev, "Optical Spatial Solitons and Their Interactions: Universality and Diversity", Science 286, 1518 (1999). CrossRef Y. Kivshar and G. P. Agrawal, Optical Solitons: From Fibers to Photonic Crystals (Academic, San Diego, 2003). P. Varatharajah et al., "Stationary nonlinear surface waves and their stability in diffusive Kerr media", Opt. Lett. 13, 690 (1988). CrossRef G. Assanto and M. Peccianti, "Spatial solitons in nematic liquid crystals," IEEE J. Quantum Electron. 39, 13 (2003). CrossRef G. Assanto, ed. Nematicons: Spatial Optical Solitons in Nematic Liquid Crystals (Wiley, 2012). CrossRef O. Bang, W. Krolikowski, J. Wyller, J.J. Rasmussen, "Collapse arrest and soliton stabilization in nonlocal nonlinear media", Phys. Rev. E 66, 046619 (2002). CrossRef X. Hutsebaut, C. Cambournac, M. Haelterman, A. Adamski, K. Neyts, "Single-component higher-order mode solitons in liquid crystals," Opt. Commun. 333, 211 (2004). CrossRef C. Conti, M. Peccianti, and G. Assanto, "Route to nonlocality and observation of accessible solitons," Phys. Rev. Lett. 91, 073901 (2003). CrossRef U. A. Laudyn, P. S. Jung, M.A. Karpierz, and G. Assanto, "Quasi two-dimensional astigmatic solitons in soft chiral metastructures," Sci. Rep. 6, 22923 (2016). CrossRef U. A. Laudyn, P. S. Jung, M. A. Karpierz, G. Assanto, "Power-induced evolution and increased dimensionality of nonlinear modes in reorientational soft matter," Opt. Lett. 39(22), 6399–6402 (2014). CrossRef Y. V. Izdebskaya, V. G. Shvedov, P. S. Jung, and W. Krolikowski, "Stable vortex soliton in nonlocal media with orientational nonlinearity," Opt. Lett. 43, 66-69 (2018) CrossRef P.S. Jung, W. Krolikowski, U.A. Laudyn, M. Trippenbach and M.A. Karpierz, "Supermode spatial optical solitons in liquid crystals with competing nonlinearities", Phys. Rev. A 95, 023820 (2017) CrossRef P.S. Jung, W. Krolikowski, U.A. Laudyn, M.A. Karpierz and M. Trippenbach, "Semi-analytical approach to supermode spatial solitons formation in nematic liquid crystals", Opt. Express 25, 23893 (2017) CrossRef S. Jungling and J. C. Chen, "A study and optimization of eigenmode calculations using the imaginary-distance beam-propagation method", IEEE J. Quantum Electron. 30, 2098 (1994). CrossRef P.S. Jung, K. Rutkowska and M.A. Karpierz, "Evanescent field boundary conditions for modelling of light propagation", Journal of Computational Science 25, 115 (2018) CrossRef A.A. Hardy, W. Streifer, "Coupled mode theory of parallel waveguides," IEEE J. Lightwave Techn. LT-3, 1135 (1985) CrossRef M. Matuszewski, B.A. Malomed, and M. Trippenbach, "Spontaneous symmetry breaking of solitons trapped in a double channel potential," Phys. Rev. A 75, 063621 (2007) CrossRef